Serological evidence of increased susceptibility to varicella-zoster virus reactivation or reinfection in natalizumab-treated patients with multiple sclerosis. (December 2015) - Kohlmann, Rebekka; Salmen, Anke; Chan, Andrew; Knabbe, Cornelius; Diekmann, Jürgen; Brockmeyer, Norbert; Skaletz-Rorowski, Adriane; Michalik, Claudia; Gold, Ralf; Überla, Klaus
Background: Serious adverse drug reactions of disease-modifying drugs in multiple sclerosis (MS) therapy may include enhanced susceptibility to reactivation of neurotropic herpes viruses like varicella-zoster virus (VZV) and the John Cunningham (JC) polyomavirus. Objective: Because symptomatic reactivation of these viruses are rare events, we determined the incidence of rises in anti-VZV IgG antibody levels as a potential marker for enhanced susceptibility to subclinical and symptomatic reactivation of neurotropic viruses. Methods: Anti-VZV IgG levels were measured in paired serum samples taken 6–8 months apart from natalizumab-treated MS patients, healthy blood donors and human immunodeficiency virus (HIV) infected patients. Results: The incidence of significant rises in anti-VZV IgG levels in natalizumab-treated MS patients was 4.26 per 100 person-years, which was significantly higher than in healthy blood donors. Retrospective evaluation of the available medical records of patients with rises of anti-VZV IgG levels did not reveal herpes zoster (i.e. shingles) manifestations. Conclusions: The increased incidence of significant rises of anti-VZV IgG levels in natalizumab-treated MS patients might indicate an association of natalizumab treatment of MS with an elevated risk of a subclinical VZV reactivation and/or reinfection events. Whether this is predictive of an increased risk of herpes zoster or even symptomatic reactivation of other neurotropic viruses remains to be determined in larger prospective studies.